AN ANALYSIS OF FIGURATIVE LANGUAGE IN SONG LYRICS OF THE ALBUM “MIDNIGHTS” BY TAYLOR SWIFT - Pelsi Santika; Syafryadin Syafryadin (Wiralodra English Journal, 2023)
This study aims to discover the figurative language and its meaning in the song lyrics used in the "Midnights" album. The data included the lyrics of all songs (13 songs) from Taylor Swift's "Midnights" album. This study employed a descriptive qualitative method as well as a content analysis design to describe types of figurative language and its meaning in song lyrics. The findings revealed that eight types of figurative language were used in the "Midnights" album's song lyrics: personification, simile, metaphor, hyperbole, irony, litotes, metonymy, and oxymoron. Personification with 12 data (12.5%), simile with 21 data (21.9%), metaphor with 25 data (26.0%), hyperbole with 15 data (15.6%), irony with 2 data (2.1%), litotes with 2 data (2.1%), metonymy with 17 data (17.7%), and oxymoron with 2 data (2.1%).It was found that metaphor is the most frequent type of figurative language used in the song lyrics of the "Midnights" album. It indicated that Taylor Swift used a lot of metaphor to create her songs in the “Midnights” album because figurative language can make a song more aesthetic, artistic, and meaningful, as well as the song lyrics in the "Midnights" album can be effective material for students to learn figurative language.